KAJIAN PERAN KELEMBAGAAN KELOMPOK TANI DALAM MENDAPATKAN MODAL USAHA AGRIBISNIS BAWANG MERAH - Sukadi, Sukadi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
The study aimed to understand the role of farmer groups to fasilitate and mediate their members, and collaborate with others, to access the agribusiness cost. Theirs study based on agro-ecosystem analysis in Tirtoharjo Village, Kretek Sub Regency, Bantul Regency on 2007.